Konvergensi Linguistik dan Negosiasi Identitas dalam Komunikasi Tionghoa-Bugis di Kabupaten Soppeng - Majadiah, Erni; Erni Majadiah (Interaction: Jurnal Sosiologi Komunikasi, 2025)
This study analyses the dynamics of communication between the Chinese and Bugis ethnic groups in Soppeng Regency using a descriptive qualitative approach with participant observation and in-depth interviews with key informants from both ethnic groups. The focus of the study is the process of communicative adaptation and the mechanisms of social integration that are built in daily interactions. The findings show multidimensional communicative adaptation, including: (1) Linguistic convergence through the adoption of the Bugis language with the internalization of the concept of mappakatau and the use of the discursive particles "je" and "ki" as markers of solidarity; (2) Hybridity of nonverbal communication in gestures, color symbolism, and the concept of time; (3) Active religious tolerance through cross-participation in celebrations and voluntary conversion in interethnic marriages; (4) Involvement in the preservation of traditional Bugis arts; (5) Economic interdependence that strengthens community cohesion. The identified communication patterns show an "adaptive integration" strategy characterised by selective adoption, reciprocal accommodation, and maintenance of core identity while developing cross-cultural communicative competence. Interethnic communication in Soppeng is harmonious due to inclusive community leadership, economic interdependence, and a shared commitment to tolerance. This study provides lessons for the development of multicultural communication in the Indonesian context.